Proteomics of ZIKV infected amniotic fluids of microcephalic fetuses reveals extracellular matrix and immune system dysregulation. Issue 1 (1st November 2021) - Sosa‐Acosta, Patricia; Melani, Rafael D.; Quiñones‐Vega, Mauricio; Melo, Adriana; Garcez, Patrícia P.; Nogueira, Fábio C.S.; Domont, Gilberto B.
Abstract: During pregnancy, the vertical transmission of the Zika virus (ZIKV) can cause some disorders in the fetus, called Congenital Zika Syndrome (CZS). Several efforts have been made to understand the molecular mechanism of the CZS. However, the study of CZS pathogenesis through infected human samples is scarce. Therefore, the main goal of this study is to identify and understand the biological processes affected by CZS development. We analyzed by a shotgun proteomic approach the amniotic fluid of pregnant women infected with Zika carrying microcephalic (MC + ) or non‐microcephalic (Z + ) fetuses compared to Zika negative controls (CTR). Several groups of extracellular matrix (ECM) proteins were dysregulated in the Z + and MC + patients, triggering an opposite dysregulation. The down‐regulation of the ECM proteins in the MC + groups can be another factor that contributes to CZS. On the contrary, the Z + group could be developing a neuroprotective response through ECM proteins up‐regulation. The neutrophil degranulation process was disrupted in the Z + and MC + groups, where the MC + groups showed a complex dysregulation. These results suggest that the microcephalic phenotypes are modulated by a down‐regulation of the ECM and the impairment of the innate immune system processes.